Pers dan Teknologi Media: Dejumalisasi di Tengah Konvergensi - Didik Supriyanto; Iwan Awaluddin Yusuf (Jurnal Komunikasi, 2007)
This article studied the latest issues of media convergence that was facilitated by the internet and mobile technology, and also its influence on conventional media. Further, the discussion developed around the implications of media convergence towards principles and practices of conventional journalism. Although some principles that were related with basic ethics continued to be maintained in accordance with the universal journalism values: accurate, objective,fair, balance, and neutral, but in practice, the presence of online journalism reduced the conventional journalism techniques. The change happened due to the role of the journalist, gatekeeper, the medium, and the audience's behavior. To clarify discussions, the author will explain Detikcom's experiences in managing online news site as an actual case.